TINJAUAN POLITIK HUKUM TERHADAP PEMBATASAN PERIODESASI JABATAN KEPALA DAERAH TINGKAT II DI ACEH - Eza Aulia (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2020)
The system of limiting periodicals for second level regional heads of office in Aceh province contains norms that limit a maximum of two terms. Therefore a legal political review is needed by aligning existing regulations with the development of state administration. The purpose of this research is to analyze in the perspective of legal politics related to the limitation of the term of office and to determine the das sollen that is in line with current legal developments. The result of the research is that the norm which limits the two terms of office was born due to the consequences of the old order government where previously the term of office was not limited. The option of limiting the term of office of the second-level regional head currently being implemented is inappropriate because the limitation does not accommodate constituent and territorial binding elements.Keywords: limitation, periods, regional head position, Aceh